Investigation of Physical, Opto-Electronics and Insulating Properties of PPPCC Liquid Crystal Molecule by Density Functional Theory (DFT) Method: A Theoretical Approach - Tikaram; Kumar, Yogesh; Kumar, Narinder (East European Journal of Physics, 2026)
In this paper, we have studied the physical, electro-optical and thermal properties of PPPCC liquid crystal molecule. Density functional theory (DFT) with the B3LYP functional and the 6-31G(d,p) basis set is employed for the optimization and analysis of the p-Propoxyphenyl trans-4-pentylcyclohexanecarboxylate (PPPCC) LC molecule. Various physical properties, such as HOMO-LUMO energy levels, electro-optical properties, and global parameters, are computed and analysed for the PPPCC liquid crystal. We have reported the birefringence of p-Propoxyphenyl trans-4-pentylcyclohexanecarboxylate (PPPCC) liquid crystal under the effect of an external electric field. The UV-Visible analysis leaves a strong peak at 252 nm due to π-π* transitions. HOMO-LUMO band gap found to be 5.1 eV. The maximum stretching was observed at 1000 cm-1 due to the C-O stretching caused by the Ether in the PPPCC liquid crystal. The C-C stretching around 1600 cm-1 is found due to phenyl group present in PPPCC. The temperature-sensitive birefringence value of PPPCC makes it a suitable choice for modern optical technology applications. The refractive index remains unchanged at large applied electric fields, making it a suitable choice for opto-electronic devices in THz applications. Due to the large band gap, this molecule could be a suitable choice for insulating applications.